METHODS AND TECHNIQUES OF DE-FAMILIARIZATION AND HIGHLIGHTING IN THE POEMS OF AHMAD SHAMLOO - SHAHRAM PANAHI, FATEMEH MODARRESI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present research by searching through the collection of Ahmad Shamloo's poems has yielded examples of a variety of normative evasions. This article shows that Shamlou is a poet who possesses a particular worldview and his deep intellectual and consistent mind has made his poetry an influential and well-crafted poem. Considering the semantic and structural aspects of Shamloo's poetry, his poems can be influenced by Hafez. Although he has dropped the weight from poetry, he has not come to terms with his deep knowledge of the word and the word when he used the word contrary to the grammatical standards in the sentence. Some of these destructive hands, which in the poetry of an illiterate poet may be a major flaw, are so well-saturated in Shamlou's poetry that they have become an excessive norm. In this essay Shamloo's poetry is examined with respect to Leach's views on the types of norm avoidance as well as the types of norm avoidance according to the definitions presented in Sima's literary culture.